2010
DOI: 10.1002/ajhb.20997
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal steroids and salivary IgA in healthy young women and men

Abstract: Empirical evidence from clinical, nonhuman animal, and in vitro studies point to links between immune function and gonadal steroids, including potential androgenic immunosuppression and estrogenic immunoenhancement. This study was designed to test links between steroids and one marker of mucosal humoral immunity-immunoglobulin A (IgA) in healthy individuals, to facilitate comparisons with other species and clinical populations, as there are few existing studies with healthy humans that also allow gender/sex in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Indeed, research shows that women's circulating estrogen levels are positively related not only to their feminine features, but also to judgments of attractiveness, femininity, and health, by opposite sex individuals (Law Smith et al, 2006;Röder, Fink, & Jones, 2013). Further, self-report and objective measures of health indices correlate positively with facial femininity and estrogen levels (Gray & Boothroyd, 2012;Thornhill & Gangestad, 2006;van Anders, 2010), and in cross-cultural examinations, preferences for facial femininity significantly correlate with the health of the nation, indicating that in hazardous environments, men may sacrifice fecundity for cues to resource holding potential . These findings align with other cultural preferences in that men migrating from resource-poor to resource-rich nations show a shift in larger body type preference to a thinner ideal (Tovée, Swami, Furnham, & Mangalparsad, 2006), suggesting that if survival is less of an immediate concern, preferences may shift towards cues of fertility.…”
Section: Men's Preferences For Facial Femininitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research shows that women's circulating estrogen levels are positively related not only to their feminine features, but also to judgments of attractiveness, femininity, and health, by opposite sex individuals (Law Smith et al, 2006;Röder, Fink, & Jones, 2013). Further, self-report and objective measures of health indices correlate positively with facial femininity and estrogen levels (Gray & Boothroyd, 2012;Thornhill & Gangestad, 2006;van Anders, 2010), and in cross-cultural examinations, preferences for facial femininity significantly correlate with the health of the nation, indicating that in hazardous environments, men may sacrifice fecundity for cues to resource holding potential . These findings align with other cultural preferences in that men migrating from resource-poor to resource-rich nations show a shift in larger body type preference to a thinner ideal (Tovée, Swami, Furnham, & Mangalparsad, 2006), suggesting that if survival is less of an immediate concern, preferences may shift towards cues of fertility.…”
Section: Men's Preferences For Facial Femininitymentioning
confidence: 99%
“…The finding that men generally prefer feminine faces (e.g., Jones et al, 2007;Komori et al, 2009;O'Connor et al, 2013) and that facial femininity is correlated with judgments of attractiveness and health by opposite sex individuals (Law Smith et al, 2006;Röder et al, 2013) as well as certain health indices and/or estrogen levels (Gray & Boothroyd, 2012;Jones et al, 2015;Thornhill & Gangestad, 2006;van Anders, 2010), longevity (Henderson & Anglin, 2003), and fertility (e.g., Jokela, 2009;Roberts et al, 2003) suggests that facial femininity may represent one such cue.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the immune effects of endogenous T are no more consistent: some show a negative association between women’s endogenous T and markers of adaptive immunity such as antibody production (Furman et al, 2014), while others show a positive association (Ding et al, 2007) or no significant association (van Anders, 2010). Studies in healthy premenopausal women have generally found that no association between endogenous T and markers of inflammation (Benson et al, 2008; Guzelmeric et al, 2007; Kelly et al, 2001; Tarkun et al, 2004); in postmenopausal women, some studies have found a positive association (Maggio et al, 2011; Maturana et al, 2008) and others, a negative association (Joffe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…7 Gender differences in sIgA levels have been reported in healthy young men and women. 8 Serum levels of IgA have not been shown to have direct relationship with those found in saliva. 7,[9][10][11] In children and the elderly, both who are at increased risk of a compromised immune system, a lower concentration of IgA in saliva has been conceptualized as a risk factor for upper respiratory tract infections (URTI).…”
Section: Immune Biomarker: Salivary Immunoglobulin-amentioning
confidence: 99%